Manufacturing Urgency: Development Perspectives on Violence Against Women - Mason, Corinne (Université d'Ottawa / University of Ottawa, 2013)
This dissertation investigates discourses of anti-violence strategies in the context of international development. While violence against women is, of course, an urgent problem, this dissertation explores how the urgency to end violence against women is socially, culturally, economically, and politically constructed. I consider the manufacturing of urgency in three case studies of contemporary anti-violence initiatives: i) American foreign policy including what has been branded as “The Hillary Doctrine” and proposed International Violence Against Women Act; ii) the World Bank’s report entitled The Cost of Violence; and iii) the United Nation’s UNiTE To End Violence Against Women and Say NO campaigns. In doing so, I argue that World Bank, the United Nations, and American foreign policies are too often technocratic, narrow, depoliticized, and are executed in an urgent manner in the interest of neoliberal economic growth, security concerns, and “feel good” aid at the expense of more holistic, effective and accountable responses to global violence against women.
Keywords: violence against women; development; urgency; transnational feminism; discourse; security; affect theory; disability studies; neoliberalism